AB INITIO STUDY OF ELECTRONIC, MECHANICAL AND OPTICAL PROPERTIES OF CH 3 NH 3 PbI 3 FOR PHOTOVOLTAIC APPLICATION - KIPKWARKWAR, TRUPHENA JEPKORIR (KABARAK UNIVERSITY, 2021)
The ever increasing need of energy in third world countries has necessitated the need for coming up with measures of seeking alternative energy sources. Solar energy is one of the most important alternative sources of energy because of its abundance in these regions. Up to this time, the use of the first and second generations solar cells made of silicon in making solar panels has notable shortcomings such as unaffordability and lack of longevity of the electric power generated. In this regard, therefore, this study purposes to establish ideal photovoltaic properties which increases the durability and efficiency of CH3 NH3 PbI3 solar cells. The purpose of this work was to study computationally the electronic, mechanical and optical properties of CH vii 3 NH3 PbI3 and its potential application in photovoltaic. The specific objectives include determining electronic, mechanical and optical properties of CH3 NH3 PbI3 from first principles and to establish the ideal properties of CH3 NH3 PbI3 for photovoltaic applications. Electronic, mechanical and optical properties of CH3 N3 PbI3 were calculated using ab initio methods specifically Quantum Espresso code. The norm conserving pseudo potential was used. Band gap was calculated as 1.58 eV which is close to the experimental value which is approximately 1.56 eV. Elastic constant parameters such as bulk modulus B, Young’s modulus E, shear modulus G and Poisson’s ratio ν were calculated using the Voigt–Reuss–Hill averaging scheme. Our calculated lattice parameter a is 6.39 Å comparable to experimental value of 6.33 Å while the Poisson’s ratio () in this work is 0.25 and experimental value is 0.28.Optical properties like real 𝜀1 and imaginary part (𝜀 2) of dependent dielectric function and absorption coefficient were calculated and discussed. The calculated values of all parameters were compared with the available experimental and theoretical values. There is a fairly good agreement between experimental data and this computational work. These findings establish systematic design rules to achieve silicon like efficiencies in a basic CH3 NH3 PbI3 perovskite solar cell.
Keywords: AB INITIO STUDY OF ELECTRONIC; MECHANICAL AND OPTICAL PROPERTIES; CH 3 NH 3 PbI 3 FOR PHOTOVOLTAIC APPLICATION